DISPENSASI NIKAH DALAM PERSEPSI APARAT KANTOR URUSAN AGAMA KOTA PALANGKA RAYA - Yusuf, Akhmad; Munib, Munib; Baihaki, Baihaki (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
This research was motivated by the provision of marriage dispensation which caused Law Number 16 of 2019 to be ineffective based on some perceptions of officials from the Office of Religious Affairs (KUA) in Palangka Raya City. So the aim of this research is to find out what is the perception of Religious Affairs Office (KUA) officials regarding the granting of marriage dispensations by the Religious Courts to applicants in Palangka Raya City? And how to realize the implementation of marriage according to the age restrictions in Law Number 16 of 2019 concerning Marriage according to officials from the Office of Religious Affairs (KUA) in Palangka Raya City? The type of research used is empirical legal research with a sociological juridical type. Meanwhile, the approach used is a socio-legal approach. The results of the research show that the perception of KUA officials regarding marriage dispensations has two opinions, first, marriage dispensations are included in the regulations in Law Number 16 of 2019 concerning Marriage, so just agree. The second opinion explains that he agrees, but with the condition that it is only for very urgent reasons. Second, to realize the implementation of marriage according to the age restrictions in Law Number 16 of 2019 concerning Marriage according to KUA officials in Palangka Raya City, by socializing it. As for how to socialize it to get good results, it must be in all fields, such as in the field of education , health, and religious events in society.